Measuring cortisol, the major stress hormone in fishes - Sadoul, Bastien; Geffroy, Benjamin (Journal of fish biology, 2019)
Stress in teleosts is an increasingly studied topic because of its interaction with growth, reproduction, immune system and ultimately fitness of the animal. Whether it is for evaluating welfare in aquaculture, adaptive capacities in fish ecology, or to investigate effects of human‐induced rapid environmental change, new experimental methods to describe stress physiology in captive or wild fish have flourished. Cortisol has proven to be a reliable indicator of stress and is considered the major stress hormone. Initially principally measured in blood, cortisol measurement methods are now evolving towards lower invasiveness and to allow repeated measurements over time. We present an overview of recent achievements in the field of cortisol measurement in fishes, discussing new alternatives to blood, whole body and eggs as matrices for cortisol measurement, notably mucus, faeces, water, scales and fins. In parallel, new analytical tools are being developed to increase specificity, sensitivity and automation of the measure. The review provides the founding principles of these techniques and introduces their potential as continuous monitoring tools. Finally, we consider promising avenues of research that could be prioritised in the field of stress physiology of fishes.